Increased Metallothionein Expression Reflects Steroid Resistance in Renal Allograft Recipients. Issue 8 (13th June 2013) - Rekers, N. V.; Bajema, I. M.; Mallat, M. J. K.; Anholts, J. D. H.; de Vaal, Y. J. H.; Zandbergen, M.; Haasnoot, G. W.; van Zwet, E. W.; de Fijter, J. W.; Claas, F. H. J.; Eikmans, M.
Abstract: Steroid‐refractory acute rejection is a risk factor for inferior renal allograft outcome. We aimed to gain insight into the mechanisms underlying steroid resistance by identifying novel molecular markers of steroid‐refractory acute rejection. Eighty‐three kidney transplant recipients (1995–2005), who were treated with methylprednisolone during a first acute rejection episode, were included in this study. Gene expression patterns were investigated in a discovery cohort of 36 acute rejection biopsies, and verified in a validation cohort of 47 acute rejection biopsies. In the discovery set, expression of metallothioneins (MT) was significantly (p < 0.000001) associated with decreased response to steroid treatment. Multivariate analysis resulted in a predictive model containing MT‐1 as an independent covariate (AUC = 0.88, p < 0.0000001). In the validation set, MT‐1 expression was also significantly associated with steroid resistance (p = 0.029). Metallothionein expression was detected in macrophages and tubular epithelial cells. Parallel to the findings in patients, in vitro experiments of peripheral blood mononuclear cells from 11 donors showed that nonresponse to methylprednisolone treatment is related to highly elevated MT levels. High expression of metallothioneins in renal allografts is associated with resistance to steroid treatment. Metallothioneins regulate intracellular concentrations of zinc, through which they may diminish the zinc‐requiring anti‐inflammatory effect of the glucocorticoid receptor. Abstract : The authors demonstrate that resistance to steroid treatment during acute renal allograft rejection is associated with high intragraft expression of zinc‐regulating metallothioneins, which may diminish the zinc‐requiring anti‐infl ammatory effect of the glucocorticoid receptor.